REGIONAL AND ACCESSIBILITY ANALYSIS OF THE BANKING SYSTEM AND THEIR IMPACTS TOWARD REGIONAL FINANCIAL INCLUSION IN INDONESIA - Asyatun, Irma (Bank Indonesia, 2018)
Financial inclusion has been widely discussed in the global level. The increased engagement in discussion of financial inclusion is inseparable from the implementation of policy priorities which are seemingly leaning towards improving financial inclusion to tackle poverty and growing inequality in a country. This article seeks to identify whether regional variables (income level, educational level, income inequality, population size and banking accessibility) are significant on influencing financial inclusion in Indonesia. This study proxied financial inclusion level by measuring the financial inclusion index using the method developed by Sarma in 2012. The research is conducted for 3 years, between 2012-2015. Employing the panel data estimation method, the results indicate that income level, educational level, and banking accessibility possess significant impact on financial inclusion in regional Indonesia.